An experimental study on oil-water slug flow in export pipelines with shallow inclined elevations. - Akarcay, Mehmet (Cranfield University, 2022)
The present study aims to better understand liquid-liquid intermittent flow regimes under different operational and flow conditions, such as flowrates of fluids, pipe inclination and fluid properties, with a focus on the pipe inclination alternating between 0° and +5°. A 0.0254m diameter pipe loop multiphase flow rig was utilised to conduct the experimental study. The fluids used for tests were tap water (pw = 997kg/m ³ and μw = 1mPa.s under the normal temperature and pressure (i.e. NTP, 15°C and 1atm) with an oil. Two different oils, EDM250 (p₀ = 811kg/m ³ and μw = 7mPa.s under the NTP) and H100 (p₀ = 878kg/m ³ and μw = 423mPa.s under the NTP) were used for tests to cover the variations in density and viscosity. It was found that less dense and viscous oils are less likely to develop intermittent flow regimes than heavier oils. In addition, regardless of the oil type present, intermittent flows are more likely to develop in a pipe with a higher degree of upwards inclination. This is particularly more effective for lighter oils because the inclination factor alters the angle between multiphase flow direction and gravity. This, in turn, aids the oil phases to intrude into the water phase region to have a greater prospect of developing and widening the relevant flow regimes envelopes such as slug and plug flows. Additionally, this thesis also proposes a modified liquid-liquid flow regime grouping method based on the modified Froude numbers. The proposed dimensionless parameter takes water hold-up variables into consideration by defining the hydraulic diameter to coincide with each phase's gravitational and inertial forces. Furthermore, correlations of pressure gradient and hold-up are also developed and presented. The developed models are then implemented with a dimensionless scale-up protocol to demonstrate scaling across laboratory experimental data generated from systems with different pipe diameter sizes. Overall, the models developed show improved performance for grouping flow patterns consistently, hence allowing for better prediction of liquid-liquid flow regimes that transition between intermittent flows. The significant outcomes of this project are the following: (1) evidence of intermittent flow regimes existing across a wide range of dual-incompressible multiphase flow conditions, (2) the development of design charts for pipelines that consider the prevention of intermittent flow regimes and (3) utilising the proposed hold-up and pressure gradient correlations with a scale-up protocol to predict larger pipeline behaviours.
Verdin, Patrick G. - Associate Supervisor
Keywords: Oil-water flow; dual incompressible; multiphase flow; liquid-liquid flow; slug flow; plug flow; intermittent flow; scale-up; flow regime grouping; pressure correlation; hold-up correlation; froude number